The Influence of Cultural Values and Individual Seller Behavior on Tourists' Interest in Visiting the Lok Baintan Floating Market - Tarisa Qathrinada; Isra Ul Huda; Rifqi Amrulloh (Eduvest - Journal of Universal Studies, 2024)
This study aims to determine the effect of cultural values and individual seller behavior on tourist interest in visiting the Lok Baintan Floating Market. The population in this study were Nusantara visitors in 2023 and a sample of 100 respondents. Data was collected by questionnaire and analyzed by multiple linear regression using spss027 for window. The results showed that cultural values, such as the uniqueness of floating market traditions and local experiences, have a significant positive influence on tourist interest. In addition, individual seller behaviors, such as friendliness, selling skills, and knowledge of local products, also have a positive effect on tourist interest. These findings underscore the importance of maintaining cultural values and improving the quality of individual seller behaviors as strategies to increase tourist interest in Lok Baintan Floating Market. The practical implication of this study is the importance of developing training programs for sellers to improve service quality and introduce cultural values to tourists. This research contributes to the understanding of the factors that influence tourist interest in traditional markets such as the Lok Baintan Floating Market.